2020
DOI: 10.1155/2020/2354108
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Intestinal Microbiota Are Associated with Islet Function in a Mouse Model of Dietary Vitamin A Deficiency

Abstract: Aims. The underlying mechanisms involved in Vitamin A- (VA-) related changes in glucose metabolic disorders remain unclear. Recent evidence suggests that intestinal microbiota is closely linked to the metabolic syndrome. Here, we explored whether and how intestinal microbiota affects glucose homeostasis in VA-deficient diet-fed mice. Methods. Six-week-old male C57BL/6 mice were randomly placed on either a VA-sufficient (VAS) or VA-deficient (VAD) diet for 10 weeks. Subsequently, a subclass of the VAD diet-fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Vitamin A deficiency may alter gut microbiota. In mice, vitamin A deficiency reduces bacteria from the Bacteroidetes phylum (to whom B. fragilis belongs to), which altered energy homeostasis of the animal overall, and resulted in glucose and insulin intolerance [181,182]. Young rats from vitamin A deficient mothers also displayed a dysbiosis of colonic mucosal microbiota, in particular with reduced members of the Bacteriodetes phylum [183].…”
Section: The Gut Microbiomementioning
confidence: 99%
“…Vitamin A deficiency may alter gut microbiota. In mice, vitamin A deficiency reduces bacteria from the Bacteroidetes phylum (to whom B. fragilis belongs to), which altered energy homeostasis of the animal overall, and resulted in glucose and insulin intolerance [181,182]. Young rats from vitamin A deficient mothers also displayed a dysbiosis of colonic mucosal microbiota, in particular with reduced members of the Bacteriodetes phylum [183].…”
Section: The Gut Microbiomementioning
confidence: 99%
“…RA signaling during endocrine specification appears to play a critical role in directing pancreatic endocrine cell fate and function [ 29 , 30 ]. Mice fed a VA-deficient diet for eight weeks had reduced β-cell mass, glucose-stimulated insulin secretion, and tissue VA levels [ 31 ]. Interestingly, VA-deficient rats treated with VA replication or RA recovered glucose-induced insulin secretion in perifused islets [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, animal studies have shown that vitamin D upregulates tight junction proteins to improve intestinal barrier integrity, reduce LPS production, and suppress hyperinsulinemia, hyperglycemia, and neuroinflammation [ 236 ]. Vitamin A supplementation has also been shown to exert beneficial effects in modulating microbiota, enhancing pancreatic β-cell activity and reducing inflammatory responses [ 237 ], though the literature is not as robust as compared to that on vitamin D.…”
Section: Effects Of Micronutrients On T2dm and Gut Microbiotamentioning
confidence: 99%